Faktor Presepsi dan Keamanan terhadap Implementasi Sistem Informasi Akuntansi Berbasis Seluler Pada UMKM di Kota Kendal - Rahayu, Sulistyo Sri; Setiyono, Taufiq Andre (Jurnal Inovasi Akuntansi (JIA), 2025)
This study aims to empirically analyze the factors influencing the mobile-based Small and Medium Enterprises (UMKM) Accounting Information System (AIS) in Kendal City. This research employs a quantitative approach with a sample size of UMKM in Kendal City and utilizes primary data. The data is analyzed using SPSS software version 22. The results of this study indicate that the perceptions of ease of use and perceived needs do not have a significant influence on the implementation of mobile-based UMKM Accounting Information Systems (AIS), meanwhile, security and performance expectation have a significant influence on the implementation of mobile-based UMKM AIS.